The Development of Nostalgia Tourism in Yogyakarta, Indonesia - ., Nurlena; ., Musadad (International Journal of Engineering and Technology, 2019)
Nostalgia is influential for the tourism industry as it revives the memories of the past. The hamlet of a very well-known gatekeeper of Merapi Volcano, Mbah Maridjan, was frequently visited by visitors as soon as the volcano eruption claimed his life. However, the instant tourist object needs an established formula to make it sustainable. Therefore, this study explored the tourism potential in the tourist object to formulate a development planning based on the concept of nostalgia tourism. The data, collected through interviews, field observation, and document review, were analyzed inductively. The analysis results suggest that the memorial site deserves to be the main attraction, which may be developed through a proposed framework (i.e., determination of the key attraction, identification of the tourism potential, and tourism development planning). This study contributes to the recent limited literature on the nostalgia tourism and to the conceptâ€™s application to a tourism development, especially, in Indonesia.Â Â